Integration of Artificial Intelligence with Studio D-ID for Development of Interactive Learning Media - Haratua Tiur Maria; Aunurrahman Aunurrahman; Urai Salam; Venny Karolina; Warneri Warneri; Debora Nuraini; Suapri Effendy; Teguh Firmansyah; Liana Liana; Fitri Pratiwi (I-Com: Indonesian Community Journal, 2025)
This Community Service Program (PKM) aims to integrate artificial intelligence with Studio D-ID in the development of interactive learning media to improve the quality of education at Ngabang District. The PKM activities are carried out at Ngabang District, West Kalimantan. The method used in this program is a workshop that involves teachers in understanding and applying Studio D-ID technology to create interactive multimedia content. The expected outcome of this activity is to provide teachers with a deep understanding of optimizing technology in the learning process and to enhance the interactivity of the learning media produced. The integration of artificial intelligence with Studio D-ID can increase interactivity in learning, encourage teacher creativity, and optimize the use of technology in the classroom, thereby providing a more engaging and relevant learning experience for students.